Kekerabatan Bahasa Jawa, Bahasa Nias, dan Bahasa Batak Toba di Kota Medan - Sidabalok, Dindasari; Ayuanda, Winda; Nasution, Khairina; Gustianingsih, Gustianingsih; Syarfina, Tengku (Universitas Lampung, 2024)
This study aims to describe the percentage of kinship and separation time between Javanese (J), Nias (N) and Batak Toba (BT) in Medan. This study used a combined qualitative and quantitative method. The type of data studied refers to the 200 vocabulary lists put forward by Swadesh. Data sources are obtained through written sources and in-depth interviews with informants. From written data sources, research reference data were obtained in Proto Austronesian (PAN) and Indonesian language versions. Then interviews were conducted with informants from each language speaker. The data collection method used is the listen and cakap method. Data analysis techniques are carried out using lexicostatistical formula calculations and glotochronology. The results of this research show that the percentage of kinship between BJ and BN is 25%, with the separation time being 3193 years ago (calculated in 2024). The percentage of BJ and BN kinship is 34% with an estimated separation time for these two languages being 2486 years ago. Then, BJ and BN have a kinship percentage of 29%, with an estimated separation time between these two languages being 2852 years ago. Based on the percentage of kinship, these three languages can be classified into the family group of One Family (Stock).Keywords: lexicostatistic, glottochronology, Javanese, Nias, Tobanese